2016
DOI: 10.1016/j.jadohealth.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Orientation Differences in Complementary Health Approaches Among Young Adults in the United States

Abstract: Purpose Lesbian, gay, and bisexual (LGB) young adults experience a wide range of health disparities, compared to heterosexuals. However, LGBs also experience many barriers to conventional healthcare, including social stigma, lack of LGB-specific knowledge among providers, and lower rates of health insurance coverage, which may limit utilization of traditional health services. Complementary health approaches (CHA) may represent an alternative to conventional care, but very little is currently known about CHA us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 34 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Over the last decade, researchers have shown an increased interest for the physical and mental health of sexual minorities (SMs), that is, individuals who identify themselves as gay, lesbian, bisexual, or have engaged in same-sex sexual behaviour (Everett, Hatzenbuehler, & Hughes, 2016;Kerridge et al, 2017;Upchurch, Krueger, & Wight, 2016). Although there are few studies, the results showed substantial health disparities between SM individuals and heterosexual peers, with a greater number of physical health symptoms and conditions (e.g., pain, dermatitis, and asthmas) and a higher risk of mental problems (e.g., depressive symptoms, suicide risk, and substance use or abuse) in SM subjects (Marshal et al, 2011;Operario et al, 2015;Strutz, Herring, & Halpern, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, researchers have shown an increased interest for the physical and mental health of sexual minorities (SMs), that is, individuals who identify themselves as gay, lesbian, bisexual, or have engaged in same-sex sexual behaviour (Everett, Hatzenbuehler, & Hughes, 2016;Kerridge et al, 2017;Upchurch, Krueger, & Wight, 2016). Although there are few studies, the results showed substantial health disparities between SM individuals and heterosexual peers, with a greater number of physical health symptoms and conditions (e.g., pain, dermatitis, and asthmas) and a higher risk of mental problems (e.g., depressive symptoms, suicide risk, and substance use or abuse) in SM subjects (Marshal et al, 2011;Operario et al, 2015;Strutz, Herring, & Halpern, 2015).…”
Section: Introductionmentioning
confidence: 99%